Process optimization of superior biosorption capacity of biogenic oyster shells nanoparticles for Congo red and Bromothymol blue dyes removal from aqueous solution: Response surface methodology, equilibrium isotherm, kinetic, and reusability studies - Adeleke A.O.; Omar R.C.; Katibi K.K.; Dele-Afolabi T.T.; Ahmad A.; Quazim J.O.; Amusa A.A.; Alshammari M.B. (Elsevier B.V., 2025)
The essential use of natural materials or microbial biomass for effective dye removal from water, combined with simultaneous antimicrobial activity, is crucial for environmental and biomedical applications. Functionalized oyster shell waste nanoparticles (OY-NPs) were synthesized and utilized for efficient biosorption of Congo red (CR) and bromothymol blue (BB) dyes from solution, exhibiting promising antibacterial properties against gram-negative bacteria, specifically Escherichia coli (E. coli), in wastewater. Employing response surface methodology and central composite design, the impact of key process variables; pH, initial concentration, time, and adsorbent doses were investigated. Characterization through scanning electron microscopy, transmission electron microscopy, Fourier transform irradiation, and x-ray diffraction analyses revealed mesoporous crystalline structures rich in CaCO3, featuring prominent functional groups such as C?O, C[dbnd]O, and O-H. Optimization of batch experiments yielded peak efficiency at pH 3.3, initial concentration of 72.34 mg/L, contact time of 84.44 min, and a dosage of 0.1 for CR and BB, achieving a desirability coefficient of 1.0. Equilibrium studies aligned with the Langmuir isotherm model determined coefficient (R2 > 0.977), while kinetic experiments correlated well with the pseudo-second-order model (R2 > 0.9). OY-NPs demonstrated optimal adsorption capacities of 84.77 and 180.61 mg/g for CR and BB, respectively, with spontaneous and endothermic removal. Reusability studies showcased consistently high adsorption efficiency over 5 cycles, highlighting the eco-friendly and recyclable potential of OY-NPs for wastewater treatment applications. The observed antibacterial activity further supports their suitability for antimicrobial applications. ? 2024 The Authors